If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8p + -6 + -3p + 2 = 15 + 2p + 2 Reorder the terms: -6 + 2 + 8p + -3p = 15 + 2p + 2 Combine like terms: -6 + 2 = -4 -4 + 8p + -3p = 15 + 2p + 2 Combine like terms: 8p + -3p = 5p -4 + 5p = 15 + 2p + 2 Reorder the terms: -4 + 5p = 15 + 2 + 2p Combine like terms: 15 + 2 = 17 -4 + 5p = 17 + 2p Solving -4 + 5p = 17 + 2p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2p' to each side of the equation. -4 + 5p + -2p = 17 + 2p + -2p Combine like terms: 5p + -2p = 3p -4 + 3p = 17 + 2p + -2p Combine like terms: 2p + -2p = 0 -4 + 3p = 17 + 0 -4 + 3p = 17 Add '4' to each side of the equation. -4 + 4 + 3p = 17 + 4 Combine like terms: -4 + 4 = 0 0 + 3p = 17 + 4 3p = 17 + 4 Combine like terms: 17 + 4 = 21 3p = 21 Divide each side by '3'. p = 7 Simplifying p = 7
| (-2x^3+4)(2x^2+5)= | | 13-10x=43-24x | | 3y-12=2(2y+44) | | (3x-3)(x-9)= | | 4(5+2)+2= | | 15x-28=-73 | | =-4x^2+5x-12 | | 7-1k=5+3k | | 18g+7=14g-9 | | 8x-12=3x+11 | | =4x^2-5x+12 | | 5a-8a+3a= | | -2d+18-4d=16 | | 2+3y=8 | | 3.3q-2.9-4.8q=2.5q-4.9 | | 6+b=7 | | 15d-8-3d=16 | | (2x^3+3x^2-1)=0 | | (3b-2)(3b^3+6b^2+2)= | | 7x=14+15x | | 4(y+4)=5(y-3) | | 6.7+12m-9.3=6.2 | | 91-3x= | | 2x*4=8 | | 2x^2+2y^2-xy+15x+30=0 | | x-15=-28 | | x^3-6x-16=0 | | (4x+3)(2x-4)= | | p^2-7p=28 | | (4x-1)/6+(2x+1)/2=2 | | 10x-9-9=14x-9+6x | | 15n+15+4n=130 |